Reflections on social research in the early stages of the COVID-19 pandemic - Pignuoli Ocampo, Sergio (MAD, 2023)
The paper presents and analyzes, the elaboration of the problems and the choices made in a systemic study of the early phase of the COVID-19 pandemic from a conceptual and methodological point of view. For this purpose, the construction of the object of study, the adoption of the sociology of risk, and the performances and difficulties offered by the sociology of society and functional differentiation are examined. In the conclusions, a balance of the integrated approach implemented is discussed.